Novel fluoride-substituted donor/acceptor polymers containing benzodithiophene and quinoxaline units for use in low–band gap solar cells. (September 2016) - Singh, Ashutosh; Singh, Ravinder; Lin, Chein-Min; Pola, Murali Krishna; Chang, Chiao-Kai; Wei, Kung-Hwa; Lin, Hong-Cheu
Graphical abstract: Highlights: A series of low–band gap conjugated polymers were synthesized by Stille reaction. Polymers exhibited absorption ranges of 300–750 nm and energy band gaps < 1.20 eV. The highest PCE value of 2.13% was obtained in the solar cell device with PC70 BM. Abstract: In this study we used Stille polycondensation to synthesize a series of low–band gap fluoride-substituted conjugated polymers containing electron-donating benzodithiophene (BDT) and electron-accepting quinoxaline (Qx) units, with the latter presenting either two or four fluoride atoms. These donor/acceptor polymers exhibited a broad absorption range (from 300 to 750 nm), with band gap energies of less than 1.20 eV (measured using cyclic voltammetry). Because of their strongly electron-donating thiophene units, the donor/acceptor polymers featuring the more highly fluorinated structures possessed the lowest band gaps (as low as 1.14 eV) and, thus, induced the greatest photovoltaic performance among these tested polymers. The highest power conversion efficiency (2.13%) was obtained from the polymer solar cell featuring an active layer of the polymerPTF2 blended with PC70 BM (1:1.5, w/w), with a short-circuit current density, open circuit voltage, and fill factor of 8.7 mA cm −2, 0.72 V, and 0.34, respectively.